Efisiensi Penggunaan Quick Response Code Indonesia Standard (QRIS) Dalam Mendukung Penjualan di Era Digital - Simanjuntak, Berliana; Putri, Aura Permata; Syahidah, Aisyah Wafa (Media Hukum Indonesia (MHI), 2024)
This research aims to determine and analyze the efficiency of using the Quick Response Code Indonesia Standard (QRIS) by banks in supporting sales in the digital era. This research also analyzes the impact of QRIS on bank operational efficiency, including the principle of confidentiality in QRIS transactions. QRIS, as a national standard for digital payments, has been widely implemented by various financial institutions to facilitate fast and safe non-cash transactions. The data used includes QRIS transaction statistics in 2024, which shows significant growth in the number of users and merchants. The research results show that using QRIS not only speeds up the payment process but also increases customer satisfaction and customer loyalty. Thus, QRIS plays an important role in driving bank sales growth amidst the ever-growing digital transformation.